2014
DOI: 10.1111/ijfs.12600
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone‐like activity of β‐casein and its effect on residual in vitro activity of horseradish peroxidase

Abstract: Summary In this study, the residual activity horseradish peroxidase was used as a novel marker of chaperone‐like activity of β‐casein under elevated temperature. It was shown that β‐casein does affect residual activity of horseradish peroxidase (HRP) depending on the concentration and molar ratio between proteins. Incubating HRP (0.1 mg mL−1) for 10 min at 72 °C resulted in residual activity of 59 ± 5%, while addition of 1 mg mL−1 β‐casein resulted in increase in residual activity up to 85 ± 1%. Increased resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…This significant finding opens up the possibility of developing an orally administered drug for the treatment of cancer (Shapira et al., 2010). In addition, β‐casein can form stabilizing complexes with substrate proteins, such as insulin, lysozyme, ethanol dehydrogenase, and catalase, inhibiting the aggregation process (Sulewska et al., 2014). Several recent studies have also found that, in addition to β‐casein, β‐casein‐related peptides have been shown to possess potential emulsifying properties (Kehoe & Foegeding, 2014).…”
Section: Bovine Milk Casein and β‐Caseinmentioning
confidence: 99%
“…This significant finding opens up the possibility of developing an orally administered drug for the treatment of cancer (Shapira et al., 2010). In addition, β‐casein can form stabilizing complexes with substrate proteins, such as insulin, lysozyme, ethanol dehydrogenase, and catalase, inhibiting the aggregation process (Sulewska et al., 2014). Several recent studies have also found that, in addition to β‐casein, β‐casein‐related peptides have been shown to possess potential emulsifying properties (Kehoe & Foegeding, 2014).…”
Section: Bovine Milk Casein and β‐Caseinmentioning
confidence: 99%